STERNOPAGUS CONJOINED TWIN MONSTER IN CROSSBRED JERSEY COW - SARMA, D K; AHMED, K; BARUAH, P M (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia in crossbred Jersey due to conjoined twin monster is reported.
Keywords: Dystocia; Twin Monster; Jersey cow